Tomato Business Integration Conduct; Is It the Impact of Marketing Structure? (Tomato Marketing Study in Manggarai Regency, East Nusa Tenggara) - Fabianus Gangkur; Ratya Anindita; Hery Toiba (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2020)
This study aimed to examine the demand for tomato SCP in Manggarai Regency. The participants were 82 farmers, 7 middlemen, and 16 retailers. The characteristics of the farmers were homogeneous in terms of having a limited area of approximately 0.1-0.5 hectares. A simple random sampling method was then used to determine the participants. Slovin’s formula was used to determine the farmer participants. The snowball sampling method was used to assess the sample of middlemen. Market structure data was analyzed by market share, and market concentration used CR4 estimates. Whereas, consumer conduct had been descriptively studied in relation to pricing strategies and business integration. Market performance estimation was made by measuring the margin and the farmer’s share. The results showed that the structure of the market for tomatoes in Manggarai Regency was oligopolistic and very concentrated. The CR4 values were as follows: middlemen (69.95 %), retailers (54.57%) and farmers (13.05 per cent). Meanwhile, the market structure affected the market conduct in which traders as price determinant and farmers as price takers. In addition, the middlemen established vertical business integration as an attempt to expand their business, dominate the market and increase their income. Oligopoly market structure and market conduct affected the tomato market in Manggarai Regency. The tomato market performance was inefficient as seen from a wide margin but having small farmer’s share. The margin values for channels I and II were Rp12.151,00 and Rp11.525,00 respectively. Whereas the farmer’s share was 36.46 percent and 39.74 percent respectively. Reflecting to the results, an accessible price information service is extremely needed for farmers to minimize asymmetry information. In addition, farmers need to maximize the role and work of farmers' groups as a joint marketing agency in order to increase their bargaining position.